(untitled) (Zaporizhzhia Historical Review, 2021)
The article covers the investigation of Cossack starshyna (higher officers) in the works by prominent Ukrainian scientist N.D. Polonska-Vasylenko. It is shown that even now many questions formed by her still lack proper historical research.